(untitled) (International Journal of Ayurveda and Pharma Research, 2021)
Adequate analgesia in postoperative period is an essential and humanitarian factor for faster recovery. Currently used analgesics are opioids and NSAIDs which have certain adverse effect. So there is need to search pain management measures from alternative science to minimise use of opioids and NSAIDs. Sushruta samhita (Sushruta’s compendium) is the oldest reference for surgery in the world. He did various surgeries including laprotomy for intestinal obstruction, perforation, rhinoplasty, cataract and so many minor surgeries like cyst, lipoma etc removal thousand years back. Certainly he managed postoperative pain also. An effort is made in this article to explore Sushruta concept of postoperative pain and its management. Also currently available online articles regarding postoperative pain management in Ayurveda are searched. By using Ayurvedic protocols, polyherbal formulations effective pain management is possible and use of NSAIDs and opioids can be minimised.